A picture of purpose: exploring veterinary students’ motivations through photo elicitation - Orchard, Ronald J.; Moreau, Cassidy; Crauer, Brad (Frontiers in Veterinary Science, 2025)
Understanding the motivations that drive veterinary students is essential for supporting their academic success, wellbeing, and professional satisfaction. This qualitative study utilized photo elicitation, a visual and narrative research method, to explore the personal, emotional, and professional “whys” of 14 veterinary students pursuing a Doctor of Veterinary Medicine (DVM) degree. Participants submitted photographs and reflective narratives describing their motivations and how these motivations supported their journeys. Thematic analysis revealed five key themes: (1) Deep Emotional Bonds with Animals, (2) Overcoming Personal Adversity, (3) The Influence of Role Models, (4) Desire to Make a Difference, and (5) Community and Service. These findings highlight the central role of formative experiences, relationships, and values in shaping students’ aspirations and perseverance. The study underscores the potential for reflective practices, such as photo elicitation, to reconnect students with their intrinsic motivations, fostering resilience and long-term satisfaction in veterinary practice. Integrating principles such as compassionate advocacy, spectrum of care, and community engagement into veterinary education may better align training with students’ values, enhancing their preparation for impactful and fulfilling careers.